Numerical Study of Nano-encapsulated Phase Change Materials on Non-Newtonian Nanofluid Flow over a Stretching Sheet (European Journal of Pure and Applied Mathematics, 2025)
This study analyzes the hydrodynamic and thermal behavior of a power-law nanofluid containing nano-encapsulated phase change materials (NEPCMs) over a non-isothermal stretching sheet. The combined effects of non-Newtonian rheology and latent heat transport due to NEPCM inclusions are formulated through boundary-layer theory and the power-law constitutive relation.The resulting nonlinear similarity equations are solved numerically using the shooting technique with Runge–Kutta integration. Results indicate that embedding NEPCM particles within the power-law nanofluid significantly enhances heat transfer through latent heat absorption and release, though it also increases wall shear stress. Higher power-law indices suppress velocity and temperature distributions, mitigating this shear enhancement. These findings reveal a competing interaction between fluid rheology and the thermal storage capacity of NEPCMs. The study offers new insights into the coupled flow and heat transfer mechanisms of NEPCM-suspended power-law nanofluids, with relevance to advanced cooling, polymer processing, and energy storage applications.
Keywords: Runge–Kutta method, NEPCM, phase change heat transfer, nanofluids, boundary layer